Contemporary Icarus: Gustav von Aschenbach’s Journey towards the Sun - Sieradzan, Anna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The point of departure for the reflections contained in this article is the motif of the sun in Tomasz Mann’s Death in Venice. Analysing the presence of the sun in the work turns out to be fruitful for distinguishing and connecting several symbolic planes, on which the issues of Death in Venice and the drama of the main character are depicted: the relationship between contemporary times and antiquity, the cultural North-South axis, the destructive power of beauty as well as the individual fate of the artist marked by decadence. The figure of the sun seems to provide material for the interpretation of the figure of Gustav von Aschenbach as an incarnation of contemporary Icarus and allows the reader to see the path which the protagonist of Death in Venice follows in a new light.